Potential of Biomass Raw Material for Biochar Production: A Review : POTENSI BAHAN BAKU BIOMASSA UNTUK PRODUKSI BIOCHAR: TINJAUAN - Rara Eka Dyla Putri; Dwi Indah Lestari; Debi Anggun Sari; Zeolita Prabu Putri; Syariful Maliki (LPPM Universitas Malikussaleh, 2025)
Biochar is a porous carbonaceous material produced from the pyrolysis of biomass under limited oxygen conditions, and it has gained widespread attention for its effectiveness in environmental remediation, soil quality enhancement, and carbon sequestration. The physicochemical properties of biochar are highly dependent on the type of biomass feedstock and the production parameters applied. Utilizing biomass waste as a raw material for biochar not only addresses organic waste management issues but also produces value-added products suitable for various applications, such as pollutant adsorption, soil amendment, and alternative fuel sources. This review aims to systematically evaluate the potential of various biomass types as biochar feedstock, focusing on the influence of feedstock composition, pyrolysis conditions, and resulting biochar characteristics on its application performance. The study integrates recent findings in the literature, demonstrating that appropriate selection of biomass—such as oil palm empty fruit bunches, sugarcane bagasse, cotton shells, lignin, and red mud—can yield high-performance biochar for heavy metal remediation, synthetic dye adsorption, and renewable energy production. This review is expected to provide a scientific foundation for developing more efficient, adaptive, and sustainable biomass-based biochar production strategies.